PENGARUH DESAIN PEKERJAAN, BUDAYA ORGANISASI, DAN GAYA KEPEMIMPINAN TERHADAP KINERJA KARYAWAN PT SUCOFINDO (PERSERO) CABANG DKI JAKARTA - Moh. Irhas L.M, (2022)
This research is a quantitative research with the aim of knowing the effect of job design, organizational culture and leadership style on the performance of employees of PT SUCOFINDO (Persero) DKI Jakarta Branch. The population in this study amounted to 172 employees, and then a sample of 63 employees was taken using the slovin formula by probability sampling with the simple random sampling method. Data collection was carried out using google form media. The data analysis technique used is inferential statistical data analysis. Data processing was carried out using SPSS version 25 software, with a significance level setting of 5% or 0,05. The results of the tests that have been carried out are that the results on the job design variable have a positive and significant effect on the employee performance variable with the results of the Tcount 2,813 > Ttable of 1,999 and the result of a significance value of 0,007 < 0,05. Furthermore, the organizational culture variable has a positive and significant effect on the employee performance variable with the results of the Tcount 2,759 > Ttable of 1,999 and the result of a significance value of 0,008 < 0,05. Next, the leadership style variable has a positive and significant effect on the employee performance variable with the results of the Tcount 3,050 > Ttable of 1,999 and the result of a significance value of 0,003 < 0,05. And simultaneously the independent variable has a positive and significant effect on the dependent variable with the results of the Fcount value of 19,944 > Ftable of 2,76, and the significance value of 0,000 < 0,05, with the results of the coefficient of determination test (R - Square Test) obtained by 0,503 or 50%, which means that 50% of employee performance is influenced by job design, organizational culture, and leadership style.